Perancangan daan Pembuatan Company Profile Berbasis Website Menggunakan CMS Wordpress pada Kafe Kajja Korean Street Food di Garut - Fadillah, Putri Natsya Nur; Gaffar, Mohammad Rizal (Ebiz Prima Nusa, 2023)
Kajja Korean Street Food is a business engaged in food and beverages. Inspired by the many fans of Korean drama films who often display the culture and culinary specialties of the country of ginseng, this is one of the backgrounds for the establishment of this Kajja Korean Street Food business. However, currently Kajja Korean Street Food only has an Instagram account to promote and introduce its food and beverage products, which is not yet effective enough to attract more consumers. Therefore, it is necessary to digitize business using a website. Kajja Korean Street Food chose to create a website-based company profile using the WordPress Content Management System (CMS). The purpose of designing and making a company profile based on this website is to attract more consumers to know about Kajja Korean Street Food products and also as a marketing content that can be used by Kajja Korean Street Food. The design stage is carried out in four stages, namely planning, analysis, design, and implementation. After that, interviews were conducted with business owners regarding the final results of the website that had been created.